Kajian Struktural Terhadap Puisi “Masyiatullah” Karya Imam Syafi’i - Izzatunisa, Muthi’ah Izzatunisa; Febriani, Nafi; Ridwan, Nur Anisa (Prosiding Konferensi Nasional Bahasa Arab, 2023)
The purpose of writing this article is to find out the intrinsic elements in Imam Syafi'i's poementitled "Masyiatullah" and to find out the overall meaning contained in this literary work. In thisarticle there are three discussions (1) Structuralism Theory (2) Working Steps of StructuralTheory (3) Structural analysis of Masyiatullah's poetry. These three discussions include severaldiscussions, namely the history of structural theory, the meaning of structural theory, the intrinsicelements of poetry, as well as the steps for structural analysis in Masyiatullah's poetry. The resultsof research from the analysis that has been carried out, this poem consists of 9 stanzas, has ashape/typography like a rectangular box because the length of each stanza is the same and hasmore or less the same number of syllables for each word. Apart from that, this poem is a poetry ofinsight or affirmation for its readers